Sensation seeking and spatial ability in athletes - Butković, Ana (2005)
Previous research has shown that both sensation seeking and spatial ability are related to sports participation. Athletes tend towards higher sensation seeking than non-athletes and high-risk sport athletes are higher sensation seekers than low-risk sport athletes. Athletes perform better than non-athletes in mental rotation task, and more successful football players have higher scores on mental rotation task than less successful ones. In general population men score higher on sensation seeking than women, and men perform better on spatial ability tasks than women. These sex differences have often been explained in terms of hormonal influences on brain organization. The aim of this study was to explore and test several hypotheses about the sensation seeking and spatial ability in athletes: 1) do sex differences in sensation seeking and spatial ability found in general population exist in athletes ; 2) is there a relationship between sensation seeking and spatial ability (both constructs have been linked with testosterone levels in males) ; 3) are there differences in sensation seeking among athletes with preferences for sports of different levels of risk. We have administered Zuckerman's Sensation Seeking Scale-V, Spatial relations test and Vanderberg Mental Rotation test to a group of 117 male and 48 female sports students. We also asked them about their preference for sports of different levels of risk based on Zuckerman's 1983 division of sports into high-, medium- and low-risk sports. Results have shown: 1) male athletes have higher scores on both tests of spatial ability than female athletes, but there were no significant differences in total sensation seeking score ; 2) male students who score higher on some sensation seeking subscales perform better on mental rotation task, but not on spatial relations task (this relation was not found in female students) ; 3) female athletes who prefer high-risk sport have higher sensation seeking scores than those who prefer medium- or low-risk sports (these differences were not found in male athletes).